Geometric and Spectral Analysis - Albin, Pierre; Jakobson, Dmitry; Rochon, Frédéric; Workshop on Geometry of Eigenvalues and Eigenfunctions; Workshop on Manifolds of Metrics and Probabilistic Methods in Geometry; Workshop "Spectral Invariants on Non-compact and Singular Spaces" (Contemporary Mathematics, 2014)
In 2012, the Centre de Recherches Mathematiques was at the center of many interesting developments in geometric and spectral analysis, with a thematic program on Geometric Analysis and Spectral Theory followed by a thematic year on Moduli Spaces, Extremality and Global Invariants.This volume contains original contributions as well as useful survey articles of recent developments by participants from three of the workshops organized during these programs: Geometry of Eigenvalues and Eigenfunctions, held from June 4-8, 2012; Manifolds of Metrics and Probabilistic Methods in Geometry and Analysis, held from July 2-6, 2012; and Spectral Invariants on Non-compact and Singular Spaces, held from July 23-27, 2012.The topics covered in this volume include Fourier integral operators, eigenfunctions, probability and analysis on singular spaces, complex geometry, Kahler-Einstein metrics, analytic torsion, and Strichartz estimates.